Phylogenetic analysis of H6 influenza viruses isolated from rosy-billed pochards (Netta peposaca) in argentina reveals the presence of different HA gene clusters - Rimondi, Agustina (2011)
Until recently, influenza A viruses from wild waterfowl in South America were rarely isolated and/or characterized. To explore the ecology of influenza A viruses in this region, a long-term surveillance program was established in 2006 for resident and migratory water birds in Argentina. We report the characterization of 5 avian influenza viruses of the H6 hemagglutinin (HA) subtype isolated from rosy-billed pochards (Netta peposaca). Three of these viruses were paired to an N2 NA subtype, while the other two were of the N8 subtype. Genetic and phylogenetic analyses of the internal gene segments revealed a close relationship with influenza viruses from South America, forming a unique clade and supporting the notion of independent evolution from influenza A viruses in other latitudes. The presence of NS alleles A and B was also identified. The HA and NA genes formed unique clades separate from North American and Eurasian viruses, with the exception of the HA gene of one isolate, which was more closely related to the North American lineage, suggesting possible interactions between viruses of North American and South American lineages. Animal studies suggested that these Argentine H6 viruses could replicate and transmit inefficiently in chickens, indicating limited adaptation to poultry. Our results highlight the importance of continued influenza virus surveillance in wild birds of South America, especially considering the unique evolution of these viruses.